PEMBERIAN PUPUK KALIUM PADA SISTEM TUMPANG SARI TANAMAN JAHE DAN JAGUNG DENGAN JARAK TANAM YANG BERBEDA - Idwar '; Husna Yetti; Herman '; Fitriani Karlita (Jurnal Sagu, 2010)
This research aimed to know the dose of pota«ium Tertilizer, phnt spacing and sawdust ash toincrease production of ginger and com planted at multiple cropping system. TMs research was conducted byCompletely Randomized Btocii Design (RAK) factorial consisted of 2 facton and 3 replications. The researchstarted on April and fmisbed on Augnst 2<m. The first factor was potaasinm fcrtlizcr with dose ofO kg KCVha, iOO kg KCI/ha, 200 kg KCI/ba, and 300 kg KCI/ha. The second factor was different plant spacmg ofginger crop which were 25 i3S cm, 30140 cm, and 35 x 45 cm. Every treatment and replication was 2 x 2 m.Parameters observed were height of ginger crop and corn crop, relative growth rate of ginger and corn,number of ginger crop, wet weight of ^nger crop, dry weight of ginger crop, the timeflowersappear of corn,dry grain weight of com crop, and weight of 100 com grains. The result of linear analysb of variant wascontinued by Duncan New Multi|rie Range Test (DNMRT) at 5 level Researchrasnhindicated that application%of potassium fertilizer with dose of 100 kg/ha and 25 x 3S cm of ginger crop spacing represented the besttreatmen t to increase production of ginger and application of potassium fertSizer with dose of300 kg/ha and30 X 40 cm, 35 x 45 cm represented (he best treatments to increase production of corn.